Acquisition of vehicles through consortium: An approach to its advantages and disadvantages - dos Santos, Thainá Carvalho; da Silva, Benedito Albuquerque (Seven Editora, 2024)
The study presents an analysis of the advantages and disadvantages related to the acquisition of goods through consortium in comparison with other financing modalities available in the Brazilian market. The study was carried out based on research and data collected from financial institutions, consortium administrators, companies in the automotive sector and consumers who have considered the consortium's option for the acquisition of a vehicle, concentrating the analysis on automotive vehicles, such as passenger cars. In this way, a view of the relevant aspects that are considered for consumer decision-making in this specific context was presented, seeking to contribute to the choice of the most appropriate vehicle acquisition modality for their needs and financial objectives, focusing on the consortium and its advantages. By considering the advantages and disadvantages of each option, consumers can make a more conscious choice, maximizing their investment and satisfaction. In the end, it was possible to conclude that although the cash purchase has a lower cost at the end of the plan, most consumers cannot have the value immediately for the purchase of the good since it can compromise the monthly family income, CDC financing and leasing are the options with the highest cost, making the consortium the most considerable option in the decision making for the acquisition of the good. DOI:https://doi.org/10.56238/sevened2024.018-042